1975
DOI: 10.1073/pnas.72.11.4592
|View full text |Cite
|
Sign up to set email alerts
|

Oncornavirus-like particles released from arginine-deprived human lymphoblastoid cell lines.

Abstract: TypeC RNA tumor virus particles were released from three different human lymphoblastoid cell lines after incubation in arginine-deficient medium. The released virus-like particles were characterized by (a) their ability to band in sucrose gradients at a density of 1.18-1.18 g/ml; (b) the presence of an RNA-directed DNA polymerase activity resembling that of the oncornaviruses; and (c) isolation of cores that and at a density of 1.26-1.27 g/ml in sucrose gradients. Examination of the arginine-deprived human lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…The possibility that, in addition to Epstein-Barr virus (EBV), an RNA tumor virus might also play a role in the etiology of Burkitt's lymphoma has been suggested by earlier investigators who showed that this tumor contains RNA related to the RNA of a murine leukemia virus (Kufe et al, 1973a), and that at least a portion of this virus-related RNA exists in particles possessing physical and biochemical features characteristic of the RNA tumor viruses (Kufe et al, 1973b). Further substantiation of this notion was obtained from studies demonstrating that arginine deprivation of two Burkitt-lymphoma-derived cell lines, Raji and P3HR-1, activated them to release oncornavirus-like particles (Kotler et al, 1975).…”
mentioning
confidence: 94%
“…The possibility that, in addition to Epstein-Barr virus (EBV), an RNA tumor virus might also play a role in the etiology of Burkitt's lymphoma has been suggested by earlier investigators who showed that this tumor contains RNA related to the RNA of a murine leukemia virus (Kufe et al, 1973a), and that at least a portion of this virus-related RNA exists in particles possessing physical and biochemical features characteristic of the RNA tumor viruses (Kufe et al, 1973b). Further substantiation of this notion was obtained from studies demonstrating that arginine deprivation of two Burkitt-lymphoma-derived cell lines, Raji and P3HR-1, activated them to release oncornavirus-like particles (Kotler et al, 1975).…”
mentioning
confidence: 94%
“…Note the irregularity and fragility of the particle membranes. (Kotler et al, 1975(Kotler et al, , 1977.…”
mentioning
confidence: 99%
“…HUMAN lymphoid cells derived from lymphoma and leukaemia patients were found to contain retrovirus genetic information and to induce the formation of type C virus particles under suitable conditions (Gallagher & Gallo, 1975;Kotler et al, 1975;Mak et al, 1974;Nooter et al, 1975). Initial studies by Kotler et al (1973Kotler et al ( , 1975 showed that cultured lymphoblastoid cell lines from patients with leukaemia and Burkitt's lymphoma produce retrovirus-like particles after incubation in arginine-deficient medium.…”
mentioning
confidence: 99%
See 2 more Smart Citations